The Extended UTAUT Acceptance Model of Computer-Based Distance Training System Among Public Sector's Employees in Jordan - Alrawashdeh, Thamer A. (2011)
The utilization of advanced network technologies and modern computer applications in distance learning raises the importance of distance learning system in the delivery of learning materials and resources to remote trainees. This innovation offers the organizations and their employees an opportunity to solve the problems associated with traditional training methods. In this respect, the acceptance of computer based distance training system (CBDTS) is considered critical in determining the success of its implementation. However, the number of studies that have been conducted to examine the acceptance of distance training system by employees of public sector organizations in the Kingdom of Jordan is very limited. It is also questionable whether the information system acceptance models that have been previously developed can be used to examine the acceptance of CBDTS by public sector employees in Jordan. Questions are also raised to the idea that perhaps there may be other factors that play important roles in this context. The main objectives of this study therefore are to determine the factors that lead to the acceptance of public sector employees on computer-based distance training system and finally to propose a model of technology acceptance of computer-based distance training system by public sector employees. A total of 600 questionnaires were distributed through a survey to public sector employees in Jordan. The study received about 386 responses, which represents 64.3% returned rate. Structural equation model (SEM) was used with AMOS version 16.0 to analyze the data. The findings indicate that six core determinants, namely, performance expectancy, effort expectancy, system flexibility, system enjoyment, social influence, and facilitating conditions significantly influenced employee intention to use distance training system. Five core determinants; system interactivity, system enjoyment, computer anxiety, computer self efficacy, and facilitating conditions significantly determine effort expectancy while only four of them including system interactivity, system enjoyment, computer anxiety, and effort expectancy significantly determine performance expectancy. Consequently, based on these findings, the final research model known as computer-based distance training acceptance model (CBDTAM) is proposed to explain and predict public sector employee’s intention in using computer-based distance training system. A comprehensive understanding of this model will assist decision makers to identify the reasons for the acceptance or resistance of computer based distance training system among public sector employees in the future and finally to support them to enhance the system’s acceptance and usage.